Work Education and Entrepreneurial Intention among the Students of Higher Secondary Schools in Imphal West District, Manipur - Singh, Khundrakpam Devananda (INDIAN EDUCATIONAL REVIEW, 2019)
India is facing a number of challenges that can be met if the country has innovative, well-educated and entrepreneurial citizens who have the spirit and inquisitiveness to think in new ways. The courage to meet and adapt to the upcoming challenges is to be developed while selecting a career during higher secondary school education of a student. The North Eastern Region (NER) of India lags behind the other parts of the country in terms of development. The region is facing the problems of unemployment, social unrest, law and order situations, lack of infrastructure, uncertainty, poor industrial establishments etc. If entrepreneurship is considered to be accelerator of growth and development, the educated youths can change their mindset from being ‘job seekers’ to ‘job providers’.